'It's not my community' ? insights from social identity theory explaining community-failure. (16th July 2008) - Mueller, Julia; Renzl, Birgit; Kaar, Alexandra
The availability of new Information and Communication Technologies (ICT) has led organisations to implement different kinds of electronic knowledge networks and communities. While the technological infrastructure connects employees in different locations and allows for learning and the flow of knowledge across traditional organisational boundaries, activity frequently falls short of expectations. This exploratory study of electronic communities in the context of a research-intensive organisation sheds light on the socio-cultural issues that accompany the top?down introduction of communities. Drawing on social identity theory, we demonstrate that a lack of common identity keeps employees from actively contributing to and exchanging knowledge in the communities. Implications for the implementation and design of communities are discussed.